Developing Big Books to Improve Young Learners' Vocabulary Acquisition - Mattarima, Siti Maria Ulfa; Toyyibah; Afifi, Nur (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
Teaching vocabulary for EFL young learners always challenges the teacher. The researchers have investigated the condition of SD Islam Pojok 2 Kediri and found that the school only provided modules in the English class, so researchers aim to develop a medium called a big book. This study is research and development, adapted from Dick and Carey and modified by Sugiono into seven steps: need analysis, designing, expert validation, revision I, try-out, revision II, and evaluation. The researchers collected the data through observation, interview, and documentation, then analyzed it using content and narrative analysis techniques. The results of the study showed that there are four topics to assemble the big books, namely daily activity, jobs, tourism places, and food. The expert validation reveals that three big books have been eligible for use, and one needs to be revised. In the try-out process, it was found that the teacher and students liked the story and illustrations of the big books. It helps the students gain new vocabulary and strengthen their existing vocabulary. To sum up, developing big books to improve young learners’ vocabulary acquisition has been successful.